DYNAMICS OF CONSUMER PRICES AND VOLUME OF TURNOVER IN RETAIL TRADE OF FOOD PRODUCTS - Svetlana Sokolov Mladenović; Igor Mladenović; Petra Karanikić (Ekonomika Poljoprivrede (1979))
This paper analyses the dynamics of consumer prices and the volume of turnover in the retail sale of food products in the Republic of Serbia in the period from 2006 to 2022. The focus of the research is on the impact of inflation and unemployment rates on the real volume of turnover of these products using multi-factor regression. The results show that inflation does not have a statistically significant impact on the real volume of turnover of most food products, while the unemployment rate has a significant negative impact. However, the exceptions are sugar-based and chocolate-based products, where price increases have a significant positive impact on turnover. This analysis provides insights into the key macroeconomic factors influencing consumer habits and market dynamics in the face of inflation and unemployment. The results of the research can serve as a basis for creating policies and strategies that will help retailers effectively manage their business in conditions of economic uncertainty.